Evaluation methods for sarcopenia in elderly patients with coronary heart disease - Kan Junpeng; Sun Ying (Guoji laonian yixue zazhi)
Coronary heart disease (CHD) is a prevalent chronic condition among the elderly, while sarcopenia represents a common geriatric syndrome. Emerging evidence suggests that the coexistence of CHD and sarcopenia is associated with an increased risk of adverse outcomes, including all-cause mortality and functional disability. Therefore, the early identification and comprehensive assessment of sarcopenia in patients with CHD are critical importance. This review aims to provide an overview of the definition and diagnostic criteria of sarcopenia, its epidemiological characteristics, the impact of sarcopenia on CHD prognosis, and methods for muscle mass evaluation. By synthesizing current knowledge, this article seeks to offer valuable insights for the prevention and management of sarcopenia in elderly patients with CHD.